2013
DOI: 10.1063/1.4829147
|View full text |Cite
|
Sign up to set email alerts
|

In situ optical observations of keyhole dynamics during laser drilling

Abstract: To better understand the laser drilling process and especially to clarify keyhole dynamics in metal drilling, a quasi-two-dimensional drilling assembly was set up with a thin sandwich structure. Keyhole dynamics coupling multiple physical processes were recorded using high-speed photography, and clear images were obtained. The formation of keyholes was found not to be a single unified process, and the whole drilling process could be divided into five stages: an initial melt ejection, mild melting, rapid drilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Zhang et al [16] and then Jin et al [18] observed the keyhole dynamics in aluminum foils placed between two GG17 glass plates and irradiated with CO 2 laser. Then, Chen et al [19] used the similar configuration for the study of keyhole drilling during the standalone laser pulse on a thin molybdenum sheet, using Nd:YAG laser. Li et al [20] used another configuration, where the fiber laser beam was equally shared between the bulk steel sheet and GG17 glass plate, which allowed approaching the plane symmetry condition of the keyhole observation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16] and then Jin et al [18] observed the keyhole dynamics in aluminum foils placed between two GG17 glass plates and irradiated with CO 2 laser. Then, Chen et al [19] used the similar configuration for the study of keyhole drilling during the standalone laser pulse on a thin molybdenum sheet, using Nd:YAG laser. Li et al [20] used another configuration, where the fiber laser beam was equally shared between the bulk steel sheet and GG17 glass plate, which allowed approaching the plane symmetry condition of the keyhole observation.…”
Section: Introductionmentioning
confidence: 99%
“…Duan et al [7] carefully analyzed the influences of pulse width, pulse energy, pulse repetition rate, trepanning velocity, trepanning diameter, beam rotation number, and assist gas pressure on melt ejection. Besides, more papers focused on the melt ejections of different targets: Trippe et al, [14] Chen et al, [15] and Zhang et al [16] observed the melt ejection dynamics in keyholes generated during laser drilling on steel, molybdenum and glass, respectively. Though with direct observation and accurate measurement, the phenomena of melt ejection can be truly described, the melt ejection mechanism is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%